The digital seeker a guide for digital teams to build winning experiences - De Datta, Raj K. (Columbia University Press, 2021)
"The internet was supposed to connect us to endless possibilities. So why do we keep ending up browsing the same old sites and best-seller lists? When sellers don't offer potential customers a compelling digital experience, consumers miss out on great products-and businesses miss a vital opportunity to grow. Raj K. De Datta, the founder of a company that powers digital commerce experiences for many of the world's biggest brands, offers an actionable playbook for companies looking to deliver better digital experiences to their customers. He shows that the success stories have three key traits: They're designed for seekers, not just customers-they don't just allow customers to buy or find something but enable them to solve a deeper problem. They're built on a digital experience platform that provides agile, personalized, scalable performance. And they're created by product-centric digital teams, not traditional organizations. The Digital Seeker distills key lessons from the compelling stories of innovative businesses: not just tech companies but companies spanning a wide range of industries, such as amusement parks, fashion, sports, distribution, and the public sector. De Datta pinpoints the power of seeker-centric philosophy-asking not simply what does someone want, but why they want it-in order to achieve transformative results. Providing a roadmap for all digital teams to adopt, this book also offers crucial insights into e-commerce challenges and opportunities during and after the COVID-19 pandemic"--